2013
DOI: 10.1007/s40003-013-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Indole Acetic Acid Production by Pseudomonas putida UB1 and its Effect as Plant Growth-Promoting Rhizobacteria on Mustard (Brassica nigra)

Abstract: Indole-3-acetic acid (IAA) production was monitored in nine plant growth-promoting rhizobacteria isolated from the rhizospheric soil of alfalfa (Medicago sativa). The isolate producing maximum amount of IAA was identified as Pseudomonas putida UB1 by 16S rRNA partial gene sequencing. Further investigations were carried out for optimal L-tryptophan concentration and other growth parameters for IAA production by P. putida. IAA production increased when the L-tryptophan medium for IAA production was supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
57
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 35 publications
17
57
0
2
Order By: Relevance
“…In the present study, each of the native strains was capable of producing IAA, and some of the observed effects were presumably due to the ability to utilise root exudates and synthesise plant growth regulators. Bharucha et al (2013) observed similar capacity in P. putida isolates from Medicago sativa.…”
Section: Discussionsupporting
confidence: 54%
“…In the present study, each of the native strains was capable of producing IAA, and some of the observed effects were presumably due to the ability to utilise root exudates and synthesise plant growth regulators. Bharucha et al (2013) observed similar capacity in P. putida isolates from Medicago sativa.…”
Section: Discussionsupporting
confidence: 54%
“…can improve the plant growth development and thus considered as an effective PGPR. Similar type of results was reported by Bharucha et al (2013), Sivakumar et al (2012) and Mia et al (2012).…”
Section: Resultssupporting
confidence: 88%
“…Diversos fatores como tempo de incubação, aminoácidos, fontes de carbono e nitrogênio interferem diretamente na produção de hormônios pelos microrganismos, como demonstrado por Bharucha et al (2013) uma máxima produção de AIA na concentração de 0,20 mg/mL de triptofano, presença de sacarose como fonte de energia e (NH 4 ) 2 SO 4 como fonte de nitrogênio em um tempo de incubação de 96 h. Os isolados estudados apresentaram uma faixa de produção do AIA de 26,4 a 591,8 μg mL…”
Section: Resultsunclassified